Analisis Vegetasi Mangrove di Desa Humusu Wini Kecamatan Insana Utara Kabupaten Timor Tengah Utara Provinsi Nusa Tenggara Timur - Gabriela Stefani Lalus; Maria M. E. Purnama; Norman P. L. B. Riwu Kaho (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
This research was conducted in the coastal area of Humusu Wini Village from September to November 2020. The aim was to determined the composition and structure as well as the diversity of mangrove vegetation in the coastal area of Humusu Wini Village, North Insana Sub-District, North Central Timor Distric. The analysis of the composition and structure of mangrove vegetation was carried out using the plot-line transect method. The number of observation plots were 17 with the plot size ranged from 2 x 2 m, 5 x 5 m, 10 x 10 m, and 20 x 20 m. Based on the results of the study, there were 6 mangrove species identified from 4 families. The family with the highest number of species is Rhizophoraceae that consist of 3 species namely Rhizophora apiculata, Rhizophora stylosa and Bruguiera gymnorhiza. The highest Important Value Index in trees level was occupied by Avicennia marina species with 140.484%, in poles level was occupied by Xylocarpus granatum species with 74.129%, while highest of Important Value Index in saplings and seedling levels was Rhyzophora apiculata with 57.994% and 49.444%, respectively. The mangrove vegetation diversity index ranged from 1,22 to 1,68, which can be categorized as moderate or fairly good of diversity index.